2017
DOI: 10.11604/pamj.2017.27.129.6855
|View full text |Cite
|
Sign up to set email alerts
|

L’embolie pulmonaire au centre hospitalier universitaire Campus de Lomé (Togo): étude rétrospective à propos de 51 cas

Abstract: IntroductionL’objectif était d’étudier les aspects épidémiologiques, cliniques et évolutifs de l’embolie pulmonaire au CHU Campus de Lomé.MéthodesC’est une étude rétrospective, analytique et descriptive sur une période de 39 mois (1erNovembre 2011- 31 Janvier 2015). Etaient inclus, tous les dossiers des patients hospitalisés dans le service de cardiologie du CHU Campus pour une EP.RésultatsLa prévalence de l’EP était de 3,1%. Le sex ratio femme/homme était de 2,2. L’âge moyen des patients était de 52,7 ± 14,4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 12 publications
4
16
0
1
Order By: Relevance
“…Pulmonary embolism is a rare condition in young African subjects. This observation was also made by Souleymane [4] in Lomé.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Pulmonary embolism is a rare condition in young African subjects. This observation was also made by Souleymane [4] in Lomé.…”
Section: Discussionsupporting
confidence: 74%
“…However, in the literature, it is World Journal of Cardiovascular Diseases more frequent in women, because of the gyneco-obstetrical risk factors added to those of men. Thus, the same observation of female predominance is made by Souleymane in Togo [4] and Diall in Mali [7]. Surgery was the dominant etiological factor (12.5%).…”
Section: Discussionsupporting
confidence: 61%
“…Pulmonary embolism is an underdiagnosed disease due sometimes to the atypical clinical presentation. In Africa, hospital studies have found a PE frequency of 3.1% at Lomé, Togo [3]. In our series, hospital frequency was 2.9%.…”
Section: Discussionsupporting
confidence: 47%
“…The venous thrombotic risk major is based on risk factors realeted to the patient that are either transient (prolonged immobilization of more than 3 days, fractures of the lower limbs in the last 3 months, travel, hormones) or permanent [9] [14]. Obesity has been recognized for decades as a major risk factor of cardiovascular and venous thromboembolic diseases [12]. As for pregnancy, the physiological changes (in particular those of hemostasis) make the pregnant woman a patient with a high thrombotic risk.…”
Section: Evolutionmentioning
confidence: 99%